Power saving through state retention in IGZO‐TFT AMOLED displays for wearable applications. Issue 4 (4th May 2017) - Steudel, Soeren; van der Steen, Jan‐Laurens P.J.; Nag, Manoj; Ke, Tung Huei; Smout, Steve; Bel, Thijs; van Diesen, Karin; de Haas, Gerard; Maas, Joris; de Riet, Joris; Rovers, Madelon; Verbeek, Roy; et al.
Abstract: We present a qHD (960 × 540 with three sub‐pixels) top‐emitting active‐matrix organic light‐emitting diode display with a 340‐ppi resolution using a self‐aligned IGZO thin‐film transistor backplane on polyimide foil with a humidity barrier. The back plane process flow is based on a seven‐layer photolithography process with a CD = 4 μm. We implement a 2T1C pixel engine and use a commercial source driver IC made for low‐temperature polycrystalline silicon. By using an IGZO thin‐film transistor and leveraging the extremely low off current, we can switch off the power to the source and gate driver while maintaining the image unchanged for several minutes. We demonstrate that, depending on the image content, low‐refresh operation yields reduction in power consumption of up to 50% compared with normal (continuous) operation. We show that with the further increase in resolution, the power saving through state retention will be even more significant. Abstract : By using an IGZO thin‐film transistor in a flexible active‐matrix organic light‐emitting diode display and leveraging the extremely low off current, we can switch off the power to the source and gate driver while maintaining the image unchanged for several minutes. Depending on the image content, low‐refresh operation yields reduction in power consumption of up to 50% compared with continuous operation.